Dynamic Analysis of Complex Composite Tubes by Continuous Element Method - Le, Thi Bich Nam; Nguyen, Manh Cuong; Tran, Ich Thinh; Duong, Pham Tuong Minh; Le, Quang Vinh (Old Journal, 2017)
This paper presents a new continuous element model for studying the dynamic behavior of complex tubes composed by cylindrical shell, annular plate and conical shell which are widely used in automobile exhausts, sewer pipes and pipelines. Based on the analytical solutions of the system of differential equations for cylinders, cones and annular plates, the dynamic stiffness matrix for complex composite tubes has been established and assembled. Natural frequencies and harmonic responses for composite tubes have been calculated and validated by comparing with the literature and with Finite Element Method. The assembly procedure of Continuous Element Method demonstrated remarkable advantages in terms of precision, volume of data storage, calculating time and larger range of studied frequencies.